Purification Simulation With Vapor Permeation and Distillation-Adsorption In Bioethanol Plant - Gozan, Misri; Setiawan, Mia Sari; Lischer, Kenny (UI Scholars Hub, 2017)
High purity of Bioethanol is required in biofuel mixing with gasoline (EXX). In bioethanol production line, the azeotropic property of ethanol-water becomes the barrier for purification process. This study examined two bioethanol separation processes by support of simulation tools, Superpro Designer 9.0 software. Ethanol purity and a low costeconomical process were the major considerations. Purification method of vapor permeation membrane technology was compared with distillation-adsorption method. Data from previous lab experiments and some literatures were used. The results showed that distillation-adsorption method is more economical compared to vapor permeation technology. Payback period of the simulation is 3.9 years and 4.3 years to distillation adsorption and vapor permeation respectively with each IRR value is 20.23% and 17.89%. Initial investment value of vapor permeation is 9.6% higher than distillation method. Significant difference observed in operating costs, since more units involved in vapor permeation require more labors to operate.